Multigroup Analysis: Stock Investment Decisions in Indonesia - Sawitri, Ni Putu Yuliana Ria Sawitri (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
This study aims to analyze the effect of financial literacy, financial inclusion, and herding behavior on investment decisions, as well as the mediating role of financial inclusion and herding behavior on the effect of financial literacy on investment decisions. The research method used is a quantitative approach using a sample of 300 investors who were selected through non-probability sampling techniques. Data were analyzed using descriptive and inferential statistics, with Structural Equation Modeling (SEM) techniques using Partial Least Square (SEM-PLS) through the Smart PLS 3.0 program. The test results show that financial literacy has a positive and significant effect on financial inclusion, financial literacy has a positive and significant effect on Herding behavior, financial literacy has a positive and significant effect on Generation X and Z investment decisions, financial inclusion has a positive and significant effect on investment decisions, Herding behavior has a positive and significant effect on Generation Y and Generation Z investment decisions, Financial inclusion is able to mediate the effect of financial literacy on investment decisions in a complementary manner in generations X and Z and full mediation in Generation Y, Herding behavior is able to mediate the effect of financial literacy on Generation Y investment decisions in full mediation, but in Generations X and Z Herding behavior does not mediate the effect of financial literacy on investment decisions. The findings of this study are useful for the development of behavioral finance theory, organism response stimulus theory, and prospect theory and are useful for stock investors in Generations X, Y, and Z, securities companies, and the Indonesia Stock Exchange in an effort to improve investment decisions.